Hypothesis Priori and A Posteriori Epistemic in Denotation and Connotation - Omer Ahmed, Trifa (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Relating Language to philosophy, this domain has a few research in Kurdish linguistics, this article (Hypothesis Priori and A Posteriori Epistemic in Denotation and Connotation), it is the first primary scientific work which presume how judging our thoughts with use lexicon our language, so that might afford logical perception in context for language. This research focuses on this question, “to what extend speaker expand their thought domain by language?” for this takes both priori and a posteriori episteme and it became measure then it related and analysis to both kinds meaning denotation and connotation. For do these, the research divided into two sections, the first section dedicated to brief illustrating epistemology, in the second section, explain how to use denotation and connotation relate priori and a posteriori episteme, then according to a verity of epistemic crowd of denotation and connotation explain the type of governing. This research depends on approach (Descriptive- Analysis) and by them receive three hypotheses as a conclusion.